A Metaphor Analysis of Recovering Substance Abusers' Sensemaking of Medication-Assisted Treatment. (July 2013) - Malvini Redden, Shawna; Tracy, Sarah J.; Shafer, Michael S.
In this study, we examined metaphors invoked by people recovering from opioid dependence as they described the challenges and successes of using medication-assisted treatment. Metaphors provide linguistic tools for expressing issues that are confusing, complex, hidden, and difficult to state analytically or literally. Using data from eight focus groups with 68 participants representing four ethnic minority groups, we conducted a grounded analysis to show how recovering substance users communicatively constructed addiction and recovery. The primary medication, methadone, was framed as "liquid handcuffs" that allowed those in recovery to quit "hustling, " get "straight, " and find "money in their pockets." Nonetheless, methadone also served as a "crutch, " leaving them still feeling like "users" with "habits" who "came up dirty" to friends and family. In this analysis, we tease out implications of these metaphors, and how they shed light on sensemaking, agency, and related racial- and class-based structural challenges in substance abuse recovery.